Effects of Extraction Solvents and pH on the Amount and Stability of Crude Color Extracted from Plants ผลของตัวทำละลายและความเป็นกรด-ด่าง ต่อปริมาณและความคงตัวของสารสีที่สกัดได้จากพืช - ไชยธาดา, ประกิต (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2019)
This research aimed to study the effects of solvents on the yields of substances extracted from natural dyes and study the stability of natural dyes at various pHs using 5 species of plants, namely, Siam weed’s leaves, Ironwood’s bark, Broken bones tree’s leaves, Jackfruit’s core, and Mangosteen’s peels. The results showed that polar solvents such as methanol and distilled water were found to be the best to extract plant-based substances such as Siam weed’s leaves and Mangosteen’s peels while non-polar solvents such as hexane were better off extracting substances from Jackfruit’s core. Besides, the study of the stability of natural dyes at various pHs by measuring the maximum absorbance with the UV-Visible spectrophotometer, having their shades compared to Munsel color chart and measuring color values with L*a*b system with the colorimeter found that each dye had different shades and intensity of dyes in various pH ranges. The Siam weed’s leaves dye extracts from all solvents had a tendency to darken the shade in the base condition. Dye extracts from Ironwood’s bark using acetone and methanol solvents were dark colored at pH equal to 12. Dye extracts from broken bones tree’s leaves using dichloromethane, acetone, and methanol as solvents appeared yellow and showed the darkest shade in methanol solvents at pH equal to 12. Similarly, dye extracts from the Mangosteen’s peels in all solvents gave the darkest shade at pH equal to 12. Dye extracts from Jackfruit’s core using acetone, methanol and distilled water as its solvents appeared dark-brown color but were not differ in each pH ranges. This research showed that solvents and pH affected the amount and intensity of natural extracts.